Novel zinc finger motif in the basal transcriptional machinery : three-dimensional NMR studies of the nucleic acid binding domain of transcriptional elongation factor TFIIS - Gozani, Shai N. (2012)
Transcriptional elongation provides a key control point in the regulation of eukaryotic gene